Grupos econômicos e responsabilidade tributária - Fonte, Leonardo Avelar da (2018)
The purpose of this paper is to examine the relationship that can be established between the formation of an economic group and the tax responsibility of the related members for the tax debts of the others. This examination is done with support of the reference system signed by the School of Logical-Semantic Constructivism, in such a way that the method employed is the analytical and hermeneutic. The subject is faced by examining the various manifestations of positive law - notably legislation and administrative and judicial precedents - and doctrine on the subject. The first part of the study is devoted to the presentation of the object and method employed. In the second part, the attention of the text falls on the subject of tax liability, therefore, in order to establish any type of conclusion within the scope of the proposed court, it is necessary to identify the essential conditions for a third party, understood as not a protagonist of the fact taxpayer, can be placed on the passive pole of a tax legal relationship (tax official). The third part of the dissertation aims to establish a definition for the expression economic group, detailing the characteristics of this object. Finally, in the final chapters, taking into account the assumptions for the creation and application of tax liability rule and the definition of economic group, the relationships that can be made and presented the final conclusions, based on the premises previously signed